Pemodelan dan Evaluasi Proses Bisnis Menggunakan Metode Quality Evaluation Framework (QEF) (Studi Kasus: CV. Mulyo Tani Makmur) - Laurensia Clara Sakti; Aditya Rachmadi; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
CV. Mulyo Tani Makmur is a manufacturing company engaged in the production of fertilizers. As a company engaged in manufacturing, then the main thing process is the production process. The production process has a major effect on the resulting production. All processes must be done correctly. However, in reality, not all processes are performed in accordance with Standard Operating Procedures (SOP). So that various things or situations can hamper the way the company to achieve targets and at risk of losses to be generated for the company. Based on the indications of emerging problems, this study evaluates the ongoing business process by adapting the Quality Evaluation Framework (QEF) method. The QEF method assists in knowing the non-conformity between the target and the calculated result. The first thing to do is to determine the non-functional requirements and core processes that are modeled using Business Process Model and Notation (BPMN) version 2.0. Then perform the calculations according to the equations in QEF based on predetermined quality factors. The result of the calculation shows whether the quality factors are appropriate or not. The inconsistencies are analyzed using the Root Cause Analysis (RCA) method to find the root cause of the problem. The results of the RCA is expected to assist the company in minimizing the problems in the running business process.